2000
DOI: 10.1016/s0032-3861(99)00256-6
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–liquid equilibria for some concentrated aqueous polymer solutions

Abstract: Vapor-liquid-equilibrium data were obtained for binary aqueous solutions of six water-soluble linear polymers in the range 70-95°C. A classical gravimetric sorption method was used to measure the amount of solvent absorbed as a function of vaporphase water pressure. Polymers studied are polyvinylpyrrolidone, polyethyleneoxide, polyvinylalcohol, hydroxyethylcellulose, polyethylenimine, polymethylvinylether.The experimental data were reduced with Hino's lattice model that distinguishes between interactions due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“… a Note: Δ (%) = 1/( N ∑[( X exp – X cal )/ X exp ] i ) × 100, where X = activity of solvent or partial pressure of solvent. b Hao et al c Palamara et al d Jung et al e Kim et al f Striolo and Prausnitz g Luengo et al …”
Section: Resultsmentioning
confidence: 99%
“… a Note: Δ (%) = 1/( N ∑[( X exp – X cal )/ X exp ] i ) × 100, where X = activity of solvent or partial pressure of solvent. b Hao et al c Palamara et al d Jung et al e Kim et al f Striolo and Prausnitz g Luengo et al …”
Section: Resultsmentioning
confidence: 99%
“…Rasmussen and Rasmussen [4] have suggested that, since PEO forms a special conformation in which the CH 2 groups are hindered from contact with the water molecules, the PEO repeat unit be defined as a single CH 2 -CH 2 -O group instead of separate CH 2 and CH 2 -O groups. As a result, in this work, new group interaction parameters between the groups H 2 O and CH 2 -CH 2 -O have been regressed using experimental data of water-PEO systems [5].…”
Section: Application To Water-peo Systemsmentioning
confidence: 99%
“…First, the group interaction parameters between CH 2 -O-CH 2 and H 2 O were regressed using the water-PEO data [5] corresponding to PEO molecular weight of 4,000,000. For this high molecular weight it can be assumed that the end-group effects are negligible.…”
Section: Application To Water-peo Systemsmentioning
confidence: 99%
“…The available thermodynamic models for the prediction of the polymer solution properties can be classified into two main categories: the lattice base and the van der Waals base models. Some models have offered based on the van der Waals theory while several authors further developed the models according to the lattice base. These bases have been applied for the expansion of various activity coefficient models as well as equations of state .…”
Section: Introductionmentioning
confidence: 99%